A prospective cohort study of presenteeism and poverty among Japanese workers during the COVID‐19 pandemic. Issue 1 (5th July 2022) - Fujino, Yoshihisa; Okawara, Makoto; Igarashi, Yu; Kuwamura, Mami; Hino, Ayako; Muramatsu, Keiji; Nagata, Tomohisa; Ogami, Akira; Ishimaru, Tomohiro; ,
Abstract: Objectives: This study examined the association of presenteeism with experiences of poverty among Japanese workers during the COVID‐19 pandemic. Methods: A prospective cohort study of Japanese workers was conducted using an Internet monitoring survey. The baseline survey was conducted in December 2020, and a follow‐up survey in December 2021. Of the 27 036 workers who participated, 18 560 (68.7%) completed the follow‐up survey. The 11 081 who reported that they were not in financial difficulty in the baseline survey were included in the analysis. The degree of work functioning impairment was assessed at baseline using the Work Functioning Impairment Scale (WFun). Households' experience of not being able to pay for food and clothing was identified in the follow‐up survey. The odds ratios (ORs) of presenteeism determined by WFun associated with poverty were estimated using a multilevel logistic model. The multivariate model included age, sex, marital status, job type, income, education, smoking, alcohol consumption, number of employees in the workplace, and the incidence rate of COVID‐19 by prefecture at baseline. Results: In the multivariate model, the odds ratio of experiencing food insecurity increased with high WFun score: compared with WFun scores of 13 or less, the OR was 1.87 (95% CI: 1.43–2.43, P < .001) for WFun scores of 14 or more and 3.26 (95% CI: 2.58–4.12, P < .001) for WFun scores of 21 or more. Conclusions: In addition to labor productivity, the adverse effects of presenteeism on social security‐related concerns such as poverty require further attention.